Mental health nursing placement: A comparative study of non-traditional and traditional placement. (November 2018) - Patterson, Christopher; Perlman, Dana; Taylor, Ellie K.; Moxham, Lorna; Brighton, Renee; Rath, Jacob
Abstract: Professional placement experiences have been considered as an approach to improving nursing attitudes towards mental health nursing and selection of mental health nursing as a career. Mental health nursing placements are now occurring in less traditional settings, however, published research of these placements remains scarce. The aim of this non-experimental comparative study was to investigate the impact of nursing student participation in a non-traditional placement, compared to participation in traditional placement. Particular focus was on the attitudes of nursing students toward mental health nursing and career preferences. Participants of the intervention group attended the non-traditional placement, (n = 23). Participants of the comparison group attended traditional placement settings (n = 27), including placements in inpatient and community mental health. The study utilised The Preplacement Survey. Results showed significant differences in scores of the non-traditional placement Recovery Camp cohort related to reduced anxiety, reduced negative attitudes, and increased preparedness for mental health. These correlated with a comparatively increased desire to pursue a future career in mental health; albeit not a statistically significant increase. Considering mental health care, in any setting, is highly dependent on the training and ability of nurses to deliver effective service, the findings of the current study are important. Highlights: Non-traditional placements can result in better preparedness for mental health nursing. Non-traditional placements can result in decreased anxiety to work with people with mental illness. Non-traditional placements can result in increased desire to pursue a career in mental health; albeit not a statistically significant increase.